Factors Affecting Teacher Organizational Commitment: A Study on Private High School Teachers in Pematangsiantar City - Efendi, Efendi; Butarbutar, Marisi; Wakhyuni, Emi; Romy, Elly; Sudirman, Acai (FKIP Universitas Lampung, 2022)
Objective The major goal of this research is to look into and analyze the elements that impact private high school teachers' organizational commitment in Pematangsiantar City. Methods: A quantitative approach-oriented research strategy is used in this study. For the collection of research data through the use of documentation equipment and the distribution of online questionnaires. The study employed a sample of 110 people to conduct the research. The purposive sampling formula is used to determine the sample, which is directed to the non-probability sampling strategy. Findings: Principal leadership, organizational environment, and interpersonal communication all have a favorable and substantial impact on teacher organizational commitment, according to this study. Conclusion: The outcomes of this study show that putting principle relational leadership into practice and changing strategy into practice can boost teachers' job commitment at the school level. Keywords: principal leadership, organizational climate, interpersonal communication, teacher organizational commitment.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202217